Improving dietary intake during lunch through the provision of a healthy school lunch at Dutch primary schools: design of a pretest-posttest effectiveness study - Ellen van Kleef; Frédérique C. Rongen; Monique H. Vingerhoeds; S. Coosje Dijkstra; Jaap C. Seidell (BMC, 2020)
Abstract Background Since there is a shift from eating lunch at home to eating lunch at primary schools in the Netherlands, providing a school lunch may be an important opportunity to improve the diet quality of Dutch children. Therefore, the aim of this Healthy School Lunch project is to encourage healthy eating behavior of children at primary schools by offering a healthy school lunch, based on the guidelines for a healthy diet. In this study, two research questions will be addressed. The first research question is: What and how much do children consume from a self-served school lunch and how do they evaluate the lunch? The second research question is: Do children compensate healthier school lunches by eating less healthy outside school hours? The purpose of this paper is to report the rationale and study design of this study. Methods In the Healthy School Lunch project children in grades 5-8 (aged 8-12 years) of three primary schools in the Netherlands will receive a healthy school lunch for a 6-month period. To answer research question 1, lunch consumption data will be collected at baseline and again at 3- and 6-months. This will be measured with lunch photos and questionnaires among children. To answer the second research question, a quasi-experimental, pre-test post-test intervention-comparison group design (3 intervention schools and 3 comparison schools) will be carried out. Potential compensation effects will be measured with a single brief questionnaire among parents at the three intervention and three comparison schools at month 6 of the lunch period. The school lunch will also be evaluated by parents (discussion groups) and teachers and support staff (brief questionnaires). Discussion Results of this study will provide valuable information to influence future school lunch interventions and policies. Trial registration This study is registered at the Netherlands trial register (NTR): trialregister.nl, Trial NL7402 (NTR7618), registered retrospectively at 2018-11-13.